Advances in Wireless, Mobile Networks and Applications International Conferences, WiMoA 2011 and ICCSEA 2011, Dubai, United Arab Emirates, May 25-27, 2011. Proceedings - Al-Majeed, Salah S.; Hu, Chih-Lin.; Nagamalai, Dhinaharan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Wireless, Mobile Networks and Applications, WiMoA 2011, and the First International Conference on Computer Science, Engineering and Applications, ICCSEA 2011, held in Dubai, United Arab Emirates, in May 2011. The book is organized as a collection of papers from WiMoA 2011 and ICCSEA 2011. The 8 revised full papers presented in the WiMoA 2011 part were carefully reviewed and selected from 63 submissions. The 20 revised full papers presented in the ICCSEA 2011 part were carefully reviewed and selected from 110 submissions.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Management information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Information Storage and Retrieval; Management of Computing and Information Systems; Electronic books